Body mass index (BMI) and outcome of metastatic melanoma patients receiving targeted therapy and immunotherapy: a multicenter international retrospective study. Issue 2 (17th November 2020) - Rutkowski, Piotr; Indini, Alice; De Luca, Matilde; Merelli, Barbara; Mariuk-Jarema, Anna; Teterycz, Pawel; Rogala, Pawel; Lugowska, Iwona; Cybulska-Stopa, Bożena; Labianca, Alice; Di Guardo, Lorenza; Del Vecchio, Michele; et al.
Abstract : Background: Obesity is a risk factor for malignancy; however, its prognostic role in patients with metastatic melanoma is controversial. We aim to investigate the prognostic role of body mass index (BMI) in patients with metastatic melanoma receiving mitogen-activated pathway kinase inhibitors (MAPKi), immune checkpoint inhibitors (ICIs) alone or their sequence. Methods: Data on patients with metastatic melanoma receiving ≥1 line of systemic treatment were retrieved from prospectively collected databases. Progression-free survival (PFS) and overall survival (OS) were analyzed by means of multivariable stratified Cox regression models; disease control rate (DCR) was analyzed by multivariable stratified logistic regression models. Subgroup analyzes according to the type of treatments received, and in BRAF -mutated patients were pre-planned. All multivariable models included BMI, age, gender, American Joint Committee on Cancer stage, performance status, lactate dehydrogenase and treatment sequencing strategy as covariates. Results: Between November 2010 and November 2018, 688 patients from three Italian and two Polish centers were enrolled. 379 (57%) patients had M1c/d disease, 273 (41%) were female and the mean BMI was 27.1 (SD=4.9). Considering first-line treatment, 446 patients (66.8%) received ICIs and 222 MAPKi. No impact of BMI on OS was detected either considering the first line of ICIs, or ICIs sequencing (HR=1.02, 95% CI: 0.99 to 1.05, p=0.202, and HR=1.02, 95% CI: 0.99 to 1.04, p=0.237, respectively). A late effect of BMI on OS was found in patients treated with MAPKi: for five units increment, a 51% of risk reduction at 18 months and a 76% of risk reduction at 30 months were observed. No significant effect of BMI on PFS and DCR was found in any of the subgroup analyzes. Conclusion: In patients with metastatic melanoma receiving ICIs, there is no impact of BMI on DCR, PFS and OS. The late prognostic effect of BMI in patients treated with MAPKi should be considered hypothesis generating and needs to be further investigated.